2020
DOI: 10.3389/fphar.2019.01580
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes Associated With the Enhanced Permeability of the Round Window Membrane Mediated by Ultrasound Microbubbles

Abstract: The round window membrane (RWM) is the most common entryway for local drug and gene delivery into the inner ear, but its permeability can change the treatment outcome. We previously demonstrated a feasible and highly efficient approach using ultrasound-aided microbubble (USMB) cavitation to enhance the permeability of the RWM. Here, we investigated the safety of USMB exposure and the association between temporal changes in RWM permeability and ultrastructure. Experimental guinea pigs were divided into two trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 39 publications
3
39
1
Order By: Relevance
“…US triggers cavitation of MBs, including inertial and stable cavitation, to produce microstreaming and shock waves in the middle ear to facilitate drug diffusion through RWM. RWM permeability is immediately increased following USMB treatment, and the enhancement of RWM permeability can persist for 72 h after USMB treatment (Shih et al, 2013 ; Lin et al, 2019 ). Electron microscopic observation of the RWM revealed heterogeneous pore-like openings and perforation on the outer epithelial layer of the RWM, indicating an acoustic cavitation-induced sonoporation effect on the RWM (Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…US triggers cavitation of MBs, including inertial and stable cavitation, to produce microstreaming and shock waves in the middle ear to facilitate drug diffusion through RWM. RWM permeability is immediately increased following USMB treatment, and the enhancement of RWM permeability can persist for 72 h after USMB treatment (Shih et al, 2013 ; Lin et al, 2019 ). Electron microscopic observation of the RWM revealed heterogeneous pore-like openings and perforation on the outer epithelial layer of the RWM, indicating an acoustic cavitation-induced sonoporation effect on the RWM (Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…RWM permeability is immediately increased following USMB treatment, and the enhancement of RWM permeability can persist for 72 h after USMB treatment (Shih et al, 2013 ; Lin et al, 2019 ). Electron microscopic observation of the RWM revealed heterogeneous pore-like openings and perforation on the outer epithelial layer of the RWM, indicating an acoustic cavitation-induced sonoporation effect on the RWM (Lin et al, 2019 ). The disruptions in the outer epithelial layer were effectively repaired, and the RWM was completely recovered within 1 month post-USMB (Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of the RWM in response to this USMB treatment method was reported more recently in a separate paper by the same group. 35…”
Section: Usmb Methods For Cochlear Drug Deliverymentioning
confidence: 99%
“…In other study, RWM damage by USMB was observed with electron microscopy with information how long the wound will be recovered. 35 In this study, we developed a new ultrasound probe with a considerably smaller diameter (1.5 mm). By using this small probe, we were able to create intense, focalized damage to the RWM with a lower ultrasound power and a smaller amount of MB solution.…”
Section: Introductionmentioning
confidence: 99%